SEJARAH HADIS DAN PROBLEMATIKA SAHABAT - Husna, Nurul (Department of Hadis Sciences (IH), Faculty of Usuluddin, Adab, and Da'wah (FUAD), State Islamic Institute of Langsa (IAIN), 2018)
If we examine the development of Hadith studies, we will find a number of Muslim and non-Muslim thinkers launching accusations against the a?dalah of the Companions of prophet muhammad peace be upon him, especially Abu Hurairah ra. Ahmad Amin for example, considered that some friends like Aisha and Ibn Abbas ra. Saying that in the history of Abu Hurairah there is a lie, because of the many narrations he memorized. All of these allegations in essence are doubtful of the problem of Abu Hurairah in particular, and friends in general. The Companions of the Prophet in the study must have a fair nature, whether all the Companions, small and large, both young and old, who are involved in the war between Ali and Mu?awiyah or not, are all fair, whereas according to the majority scholars such as Imam Abu Hanifah, Syafi?i, Malik, Ibn Hanbal, al-Bukhari, Muslim, Ibn Taymiyah and so on that all friends are fair. Friends are all fair but even so, it does not mean that a just person is the infallible person of sin and error, but obedience to him is more dominant so that he can avoid small sins and stay away from big sins.